2012
DOI: 10.1089/ars.2011.4281
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Based Regulation of Apoptosis: S-Glutathionylation As a Regulatory Mechanism to Control Cell Death

Abstract: Significance: Redox-based signaling governs a number of important pathways in tissue homeostasis. Consequently, deregulation of redox-controlled processes has been linked to a number of human diseases. Among the biological processes regulated by redox signaling, apoptosis or programmed cell death is a highly conserved process important for tissue homeostasis. Apoptosis can be triggered by a wide variety of stimuli, including death receptor ligands, environmental agents, and cytotoxic drugs. Apoptosis has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 88 publications
0
64
0
Order By: Relevance
“…Several studies (Anathy et al, 2012;Cooper et al, 2011;Dalle-Donne et al, 2009;Lim et al, 2010) have suggested that protein glutathionylation can provide a reversible switch that can regulate protein function and potentially regulate pathways in a manor analogous to protein phosphorylation. We have previously shown that GSTO1-1 can catalyse glutathionylation cycle reactions (Menon and Board, 2013) and in this study we found that total glutathionylation of proteins was significantly elevated in GSTO1-1-knockdown cells compared with wild-type and non-silencing control cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Anathy et al, 2012;Cooper et al, 2011;Dalle-Donne et al, 2009;Lim et al, 2010) have suggested that protein glutathionylation can provide a reversible switch that can regulate protein function and potentially regulate pathways in a manor analogous to protein phosphorylation. We have previously shown that GSTO1-1 can catalyse glutathionylation cycle reactions (Menon and Board, 2013) and in this study we found that total glutathionylation of proteins was significantly elevated in GSTO1-1-knockdown cells compared with wild-type and non-silencing control cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know which protease is involved in the degradation of TK2 and what implications this may have on mitochondrial function. It is likely that the relevant proteases are either induced or activated in response to oxidative stress and are involved in the redox regulation of mtDNA replication and maintenance (32,33).…”
Section: Variable DC Variable Atp/fixed Dcmentioning
confidence: 99%
“…However, a recent body of evidence has emerged in support of a critical regulatory role of oxidants in biologic processes, exerted in part through controlled oxidations of regulatory cysteines within proteins. Protein S-glutathionylation is an example of such cysteine oxidation that under physiologic conditions can be reversed by the protein thiol oxidoreductase, Grx (6). To date, virtually no information exists with regard to the role of Grx1 in the pathogenesis of infectious lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…S-glutathionylation is an oxidative modification of protein cysteines that regulates structure and function (6). We have demonstrated that oxidative modification of Fas in the form of S-glutathionylation (Fas-SSG) enhances its ability to form the death-inducing signaling complex and accelerates apoptosis in epithelial cells.…”
mentioning
confidence: 99%